Mental health of health professionals: the illness of those who are dedicated to caring for the illness of others (Research, Society and Development, 2020)
This article aims to discuss about the illness of health professionals, addressing the significant increase in the development of common mental disorders in these professionals. This subject has not yet gained a notorious attention of Brazilian society for this population, which requires care about their mental health, especially in their workplace. A non-systematic literature review study was conducted for the second half of 2019, using the Scientific Electronic Library Online (Scielo) and Latin American and Caribbean Health Sciences Literature (LILACS) databases. After analyzing the data, it was found that it is necessary to consider the specificities that are in this area, care and cure, as these specialists experience numerous stressful situations within the workplace, where their role as caregiver is always evoked for the treatment of the other. Therefore, prevention and shelter are seen as needs to create a healthy work environment, thus enabling the opening of a listening channel for these workers who are suffering.